2021
DOI: 10.3389/fsurg.2021.631419
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transforaminal Endoscopic Decompression for Lumbar Lateral Recess Stenosis

Abstract: Objective: The aim of this study was to evaluate the treatment efficacy of lateral spinal stenosis through the decompression of the nerve root under a multiple planar endoscope.Methods: From January 2017 to March 2019, 52 patients with lumbar spinal stenosis or lumbar spinal stenosis combined with intervertebral disc herniation had been treated via transforaminal approach spinal endoscopy. Our study retrospectively analyzed the treatment outcome. All patients experienced complications with different degrees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Lumbar interbody fusion (LIF) is one of the most common surgeries performed on the spine, with tremendous advances in minimally invasive techniques over the last few decades. 11 , 12 Specifically, the percutaneous method of access has expanded over the years to cover decompression, 8 , 13 fixation, 14 , 15 , 16 and recently, fusion. 7 , 17 One of the longstanding criticisms of percutaneous access for LIF are the increased rates of pseudoarthrosis likely secondary to the restricted access afforded to not only decorticate, but place bone graft and interbody cages, despite techniques improving over the years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar interbody fusion (LIF) is one of the most common surgeries performed on the spine, with tremendous advances in minimally invasive techniques over the last few decades. 11 , 12 Specifically, the percutaneous method of access has expanded over the years to cover decompression, 8 , 13 fixation, 14 , 15 , 16 and recently, fusion. 7 , 17 One of the longstanding criticisms of percutaneous access for LIF are the increased rates of pseudoarthrosis likely secondary to the restricted access afforded to not only decorticate, but place bone graft and interbody cages, despite techniques improving over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Transforaminal lumbar interbody fusion (TLIF) has been explored with a percutaneous approach in recent years with and without endoscopy. 7 , 8 , 9 A clinical trial with an investigative percutaneous delivery system for a unique implant is underway in the cervical spine (NCT04229017). Although traditional screws have been delivered to the lumbar spine percutaneously, the use of these instruments (CORUS™ Spinal System-X; DI # 00852776006508) to supplement TLIFs with facet joint decortication has not been documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, a broad range of surgical approaches for this type of decompression have been used, ranging from standard open laminectomies to endoscopic approaches using minimally invasive techniques. [34][35][36] Our group described a series of patients with symptomatic unilateral LRS who were treated successfully using interlaminar endoscopic decompression techniques. 17 Additional studies have demonstrated favorable clinical results comparing full-endoscopic with microsurgical techniques and highlighted the reduced approach-related morbidity afforded by a full-endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…6 Now, it has been gradually applied to LSS treatment. 7,8 While providing effective decompression, the spinal endoscope is less traumatic and costly. 9 It can be done under local anesthesia, 10,11 effectively decreasing postoperative complications and making it more suitable for the elderly.…”
Section: Introductionmentioning
confidence: 99%